Chinese Data Governance and Trade Policy: From Cyber Sovereignty to the Quest for Digital Hegemony? - Borgogno, Oscar; Savini Zangrandi, Michele (Journal of Contemporary China, 2024)
The article builds on an up-to-date overview of the data governance framework developed by the People's Republic of China to gauge its influence over digital trade policy at the global stage. China has developed a peculiar data governance architecture, predicated upon domestic security. The party-state has been open to discuss only trade-related aspects of information flows while shielding national autonomy from international harmonization. This strategy is coupled with the effort to project China's data governance approach externally both through China's role in international standard setting and via new digital infrastructure, through the Digital Silk Road initiative. In this respect, China's attempts to facilitate penetration by its own companies in foreign digital infrastructure needs to be assessed against the large data access power enjoyed by the state-party vis-à-vis domestic big tech companies. The article argues that such a strategy appears in contrast with the explicit commitment to protect national self-determination, especially when host countries lack adequate legal and administrative safeguards to tackle the economic and data protection challenges brought by digitalization.